The Gypsy Baron (1885) as a musical monument remembering Maria Theresa? Facts, issues, controversies (Povijesni prilozi (Historical Contributions), 2019)
The paper shows how Maria Th eresa’s legacy was remembered and highlighted alreadyin the late 19th century within the realm of musical culture. Focusing on the genre ofoperetta and taking The Gypsy Baron (1885) by Johann Strauss II (1825-1899) as anexample the paper touches upon the issues of propaganda and collective memory asconjured up by musical theatre. Considered ‘a musical monument to the Austro-HungarianEmpire’ The Gypsy Baron (originally Der Zigeunerbaron) ultimately reveals theposition the “King” Maria Th eresia cherished in the 19th century Empire, being at thesame time a fine example of the legacy of her politics. The pillars of the operetta’s plotare wars fought by Austrians: the Austro–Turkish War and the War of the Austrian Succession(1740-1748). The operetta is clearly the work inscribed into the specific politicalsituation of the late 19th century and constituted a musical response to concrete needsstimulated by civil attitudes. Hence the situation depicted in The Gypsy Baron reflectsthe multi-ethnic diversity of Habsburg Empire and the operetta’s overall message isto glorify the cooperation between various nations as (supposedly) facilitated underMaria Theresa’s reign.